2020
DOI: 10.1161/strokeaha.119.027348
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Circular RNAs as Biomarkers for the Diagnosis and Prediction of Outcomes in Acute Ischemic Stroke

Abstract: Background and Purpose— Circular RNAs (CircRNAs) show promise as stroke biomarkers because of their participation in various pathophysiological processes associated with acute ischemic stroke (AIS) and stability in peripheral blood. Methods— A circRNA microarray was used to identify differentially expressed circulating circRNAs in a discovery cohort (3 versus 3). Validation (36 versus 36) and replication (200 versus 100) were performed in independent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 8 publications
2
104
1
Order By: Relevance
“…Our results also support previous findings that circRNAs can serve as novel diagnostic biomarkers and promising therapeutic targets for IS 26,[36][37][38][39] . In the present study, based on the results of bioinformatic analyses, three of the top ten significantly DE circRNAs were selected for PCR validation in AIS patients and healthy controls.…”
Section: Discussionsupporting
confidence: 91%
“…Our results also support previous findings that circRNAs can serve as novel diagnostic biomarkers and promising therapeutic targets for IS 26,[36][37][38][39] . In the present study, based on the results of bioinformatic analyses, three of the top ten significantly DE circRNAs were selected for PCR validation in AIS patients and healthy controls.…”
Section: Discussionsupporting
confidence: 91%
“…As reported in our previous research, circFUNDC1 has been verified to be important biomarker in stroke diagnosis and prognosis [12]. Our present study furtherly illustrated that the incidence of SAI increased with increasing level of circFUNDC1.…”
Section: Discussionsupporting
confidence: 89%
“…As for the origins of elevated circFUNDC1 in plasma, our previous research has shown that no significant increase of circFUNDC1 levels was found in platelets and granulocytes of AIS patients compared with healthy controls [12]. However, the current study demonstrated that circFUNDC1 was enriched in platelets meaning that platelets might be important origins of circFUNDC1 in plasma.…”
Section: Discussioncontrasting
confidence: 62%
“… 31 , 32 , 33 Furthermore, certain circRNAs have been proposed as transcriptional and translational regulators in pathological aspects of several cerebrovascular diseases. 34 , 35 Previous studies have shown that the circRNA DLGAP4 ameliorates ischemic stroke. 36 However, the role of the circRNA circUCK2 has not been evaluated in ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%